Efforts to Transform Students' Effective Values in Social Studies Learning at SMP Negeri 25 Bengkulu City, Bengkulu Province - Riantono, Riantono; Adisel, Adisel; Nurniswah, Nurniswah (Jurusan Pendidikan Teknik Elektro, 2025)
​​​This study aims to describe the efforts of teachers to transform students’ affective values through Social Studies (IPS) learning and to identify the obstacles faced during the process in SMP Negeri 25 Bengkulu City, Bengkulu Province. Bengkulu Province. This study adopted a qualitative descriptive method using a field study approach. Data were collected through interviews, observations, and document analysis involving ten informants consisting of teachers, students, and the school principal. The data analysis followed Miles and Huberman’s interactive model, including data reduction, display, and conclusion drawing. The results showed that affective value transformation is carried out through integrated approaches, such as the incorporation of values into teaching materials, active learning methods (case studies, group work), and teacher modeling in daily behavior. Supporting programs, including Clean Friday and social projects, strengthen students’ habituation of moral values, such as tolerance, honesty, cooperation, and environmental awareness. However, the process remains gradual and uneven due to limited instructional time, low student awareness, a lack of standardized affective assessment instruments, and insufficient parental support. The study concludes that effective transformation of affective values requires the synergy of schools, teachers, and families, as well as the development of contextual learning media and systematic evaluation instruments to ensure sustainable moral internalization among students.​​